(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
Heavy metals are important environmental pollutants and many of them are toxic even at very low concentration. Toxic mental contamination of sail, aqueous, waste streams a major environmental and human health problem which is still in need of on effective and a fordable technological solutions large quantities of heavy metals are present in many regions of the globe. These metals include copper magnesium and iron. Many free floating emergent and submerged spices have been identified as potential accumulators of heavy metals due to these toxic metals phy-to-toxicity in plants are seen. The water bodies are major life reporting systems facing ecological degradation today due to irrational human inter feryence and unsustainable development keywords heavy metals, dhanpura village.